KEMASAN CERDAS PENDETEKSI KEBUSUKAN FILET IKAN NILA - Bambang Riyanto; Akhiruddin Maddu; Yogi Waldingga Hasnedi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2010)
Smart packaging that can detect the level of quality deterioration of fish is a new inspiration in providing the sense of practicality, quality assurance and food safety of fishery products in the future. Analysis of optical characteristics and dynamic nature of the response to the smart packaging with 48 mL chitosan-acetic 1% (w/v), 48 mL polyvinyl alcohol 1% (w/v) and 4 mL bromthmol blue indicator 0.2% based shows the real trend in detecting spoilage rate of tilapia fillet. Smart packaging visually can provide patterns of color changes from yellow to dark yellow next turn into green and the last become turquise during the process of fish spoilage. The spoilage rates observed of tilapia fillet with a parameter test value TVBN and TBC, showed the same tendency in detecting spoilage rate tilapia fillet, where the TVBN rate increased from 8.40+_0.40 mg N/100 g at the 0 hour to 52.36+_1.98 mg N/100 g at 15 hours and TBC rates from log 4.35+_0.07 (2.3x10 pangkat 4) CFU/g at the 0 hour to log 9.11+_0.05 (1.3x10 pangkat 9) CFU/g log at 15 hours.Keywords: fish spoilage, smart packaging, tilapia fillet.